2023
DOI: 10.5194/wcd-4-265-2023
|View full text |Cite
|
Sign up to set email alerts
|

Similarity and variability of blocked weather-regime dynamics in the Atlantic–European region

Abstract: Abstract. Weather regimes govern an important part of the sub-seasonal variability of the mid-latitude circulation. Due to their role in weather extremes and atmospheric predictability, regimes that feature a blocking anticyclone are of particular interest. This study investigates the dynamics of these “blocked” regimes in the North Atlantic–European region from a year-round perspective. For a comprehensive diagnostic, wave activity concepts and a piecewise potential vorticity (PV) tendency framework are combi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 80 publications
2
15
0
Order By: Relevance
“…Our findings are in line with the climatological evidence regarding the chain of physical processes by which LHR can affect blocking (e.g., Grams & Archambault, 2016; Hauser et al., 2023b; Pfahl et al., 2015; Steinfeld & Pfahl, 2019; Teubler et al., 2023). We conclude that there is a strong link between the correct representation of local WCB activity in the North Atlantic‐European region and the correct representation of the large‐scale circulation around EuBL onsets in NWP models.…”
Section: The Importance Of Accurate Wcb Predictionsupporting
confidence: 90%
“…Our findings are in line with the climatological evidence regarding the chain of physical processes by which LHR can affect blocking (e.g., Grams & Archambault, 2016; Hauser et al., 2023b; Pfahl et al., 2015; Steinfeld & Pfahl, 2019; Teubler et al., 2023). We conclude that there is a strong link between the correct representation of local WCB activity in the North Atlantic‐European region and the correct representation of the large‐scale circulation around EuBL onsets in NWP models.…”
Section: The Importance Of Accurate Wcb Predictionsupporting
confidence: 90%
“…Overall, our findings further motivate the relevance of weather regimes diagnostics for subseasonal‐to‐seasonal prediction and climate model analyses. A particular focus on understanding the processes that govern the behavior of the North American regimes and their lifecycles, as has been performed for the Atlantic‐European regimes (e.g., Hauser et al., 2023; Michel & Rivière, 2011; Teubler et al., 2023), would help to link the dynamical systems analyses herein with physical atmospheric variability.…”
Section: Discussionmentioning
confidence: 99%
“…Michel & Rivière, 2011;Teubler et al, 2023), would help to link the dynamical systems analyses herein with physical atmospheric variability.…”
mentioning
confidence: 99%
“…Rivière and Drouard, 2015), which is closely related to blocking over Greenland (e.g., Woollings et al, 2010). The breaking of upper-level Rossby waves (further referred to as RWB) has been found as a formation mechanism for blocking over Greenland with predominantly cyclonic RWB towards Greenland (Benedict et al, 2004;Woollings et al, 2008; results on the importance of moist-baroclinic processes by adopting the Eulerian perspective of Teubler et al (2023) into a new quasi-Lagrangian perspective. Previous studies have partly used quasi-Lagrangian approaches to investigate the role of eddy feedback on blocks and, in particular, the role of transient anticyclonic eddies (e.g., Shutts, 1983;Yamazaki and Itoh, 2013;Suitters et al, 2023).…”
mentioning
confidence: 99%
“…Previous studies have partly used quasi-Lagrangian approaches to investigate the role of eddy feedback on blocks and, in particular, the role of transient anticyclonic eddies (e.g., Shutts, 1983;Yamazaki and Itoh, 2013;Suitters et al, 2023). By tracing back negative, upper-tropospheric PV anomalies linked to a block over Europe and investigating the relative contributions of dry and moist dynamics using the same piecewise PV tendencies of Teubler et al (2023), the quasi-Lagrangian approach of Hauser et al (2023b) revealed a non-local development of the negative PV anomaly over the western North Atlantic. This negative PV anomaly propagated eastward and was pulse-like amplified by moist processes over the North Atlantic -a development the Eulerian perspective missed as the PV anomaly was located and associated processes beyond the blocking region which the Eulerian perspective focuses on.…”
mentioning
confidence: 99%